2012
DOI: 10.5923/j.nursing.20110101.01
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Sleep Behavior of Primary School-aged Children in Macao

Abstract: The school performance of students will definitely be affected if they have inadequate time to sleep. This study explored the factors influencing the sleep health. Fourteen children and their parents were invited to share their experiences, which were obtained through interviews that relied on semi-structured questions. The participating students ranged from grade 1 to grade 6 in primary schools. The 2 major themes discovered were sleep behavior and inadequate sleep. Sleep behavior appeared to be related to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
(24 reference statements)
1
1
1
Order By: Relevance
“…And it’s consistent with studies done in Nepal (23.1%), and the Upper East Region of Ghana (18%) [2, 26]. The current prevalence of pre-lacteal feeding is higher than a study done in Benin City, Nigeria (11.7%), and Ethiopian studies conducted in Arbaminch zuria district (8.9%), Enderta district (12.8%),Jimma (12.6%) [12, 1517]. This variation might be due to the difference in culture, the population character, and geographic distribution.…”
Section: Discussionsupporting
confidence: 83%
“…And it’s consistent with studies done in Nepal (23.1%), and the Upper East Region of Ghana (18%) [2, 26]. The current prevalence of pre-lacteal feeding is higher than a study done in Benin City, Nigeria (11.7%), and Ethiopian studies conducted in Arbaminch zuria district (8.9%), Enderta district (12.8%),Jimma (12.6%) [12, 1517]. This variation might be due to the difference in culture, the population character, and geographic distribution.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, a study done in Nigeria and Uganda showed that there was a positive association between levels of maternal education and nutritional indices [29, 32]. A study from Jimma in Ethiopia reported no statistically significant association between child nutritional status and education status [33]. In our study 71.4 % of mothers had no education.…”
Section: Discussioncontrasting
confidence: 51%
“…A study from Jimma also reported that there was no significant association between any of the nutritional indices and mothers’ age, education, religion, residence or the sex of the child [33]. …”
Section: Discussionmentioning
confidence: 99%